North Pole South Pole: The epic quest to solve the great mystery of Earth’s magnetism - Petrey, Allen (New Zealand Science Review, 2011)
​North Pole South Pole is the biography of geomagnetism: the story of a quest that has occupied scientific geniuses throughout the past millennium. This absorbing book explores the inner workings of our planet and its magnetic shield and is clearly written and beautifully illustrated.